Negative correlation between cerebrospinal fluid FGF21 levels and BDI scores in male Chinese subjects - Liu, Yanlong; Wang, Meiling; Tan, Xiaohua; Wang, Xiaofang; Yang, Xiaoyu; Xiao, Jian; Li, Xiaokun; Wang, Fan (Psychiatry research, 2017)
Fibroblast growth factor 21 (FGF21) is an important metabolic regulator of glucose homeostasis and lipid metabolism. Recently, FGF21 has been shown to play a robust neuroprotective role and act as a mediator of the effects of mood stabilizers. In the present study, we measured the concentration of FGF21 in human cerebrospinal fluid (CSF) and investigated the relationship of FGF21 levels with depression and anxiety emotions. Sixty-seven Chinese volunteers were recruited from Beijing Jishuitan Hospital. A significant negative association was found between CSF FGF21 levels and Beck Depression Inventory (BDI) scores in male subjects. Our findings provide evidence of the role of FGF21 in mood regulation. •FGF21 levels showed no considerable interindividual variations, ranging from 73.2 to 239.8pg/ml.•A significant association was found between CSF FGF21 levels and BDI scores in male subjects.•The present study provides evidence of the role of FGF21 in mood regulation.